Kurtosis based blind source extraction of complex noncircular signals with application in EEG artifact removal in real-time - Javidi, Soroush; Mandic, Danilo; Cheong Took, Clive; Cichocki, Andrzej (Frontiers in Neuroscience, 2011)
A new class of complex domain blind source extraction (BSE) algorithms suitable for the extraction of both circular and noncircular complex signals is proposed. This is achieved through sequential extraction based on the degree of kurtosis and in the presence of noncircular measurement noise. The existence and uniqueness analysis of the solution is followed by a study of fast converging variants of the algorithm. The performance is first assessed through simulations on well understood benchmark signals, followed by a case study on real-time artifact removal from EEG signals, verified using both qualitative and quantitative metrics. The results illustrate the power of the proposed approach in real-time blind extraction of general complex-valued sources.